ORIGINALITY OF THE TEXRS OF SHAKESPEARE'S DRAMAS AND THEIR TRANSLATION INTO UZBEK - Fayziyeva.K.,; Boboyorova Marjona Akbar qizi, (TADQIQOTLAR, 2026)
Abstract This article explores the originality of the texts of William Shakespeare's dramas and  examines  the  challenges  and  strategies  involved  in  translating  his  works  into Uzbek. It analyzes the literary and linguistic features that contribute to the uniqueness of Shakespeare's writing, including his use of language, poetic devices, and cultural references. The study also assesses how these elements are preserved or adapted in Uzbek translations, highlighting the importance of maintaining the playwright's artistic intent and emotional impact.